Landscape composition and orchard management effects on bat assemblages and bat foraging activity in apple crops - Marcos Miñarro; Daniel García (Ecosphere)
Abstract Bats are acknowledged as suppliers of essential ecosystem services such as insect pest control in agroecosystems. Little is known, however, on how bat assemblages respond to the gradients imposed by anthropogenic landscapes and farming practices and how these environmental effects translate into changes in bat foraging. In this study, we use cider apple crop in northern Spain as a model to address the filtering effects of landscape composition and orchard management on, simultaneously, quantitative and qualitative characteristics of bat local assemblages and their foraging activity. For that, we carried out acoustic monitoring of bats and sampled pest moth abundance across a wider range of apple orchards covering different landscape contexts and local management conditions. We found that bat assemblages markedly varied across orchards, according mostly to landscape composition gradients but with contrasting landscape effects on different assemblage characteristics. Namely, higher levels of rural urbanization and lower cover of seminatural woody habitats around orchards promoted bat total activity and the number of bat species/species complexes. However, this also altered bat assemblage composition, increasing dominance by the most abundant species, and decreased bat functional diversity. Additionally, a greater cover of apple tree canopy within the orchards decreased bat total activity. Landscape gradients led into predictable variations of bat foraging activity, suggesting a potential persistence of pest control services even in landscapes with limited seminatural habitat cover. The present study highlights the differential responses of bat assemblages to apple crop landscape and orchard‐scale conditions, hindering the establishment of straightforward management guidelines. Further analysis on the relationship between bat assemblage characteristics and pest control is necessary to understand how ecosystem services can be promoted through management in the apple agroecosystem.